A novel environmentally friendly method in solid phase for in situ synthesis of chitosan-gold bionanocomposites with catalytic applications. (1st March 2019) - Bonardd, Sebastián; Saldías, César; Ramírez, Oscar; Radić, Deodato; Recio, Francisco J.; Urzúa, Marcela; Leiva, Angel
Graphical abstract: A novel environmental friendly method to obtaining bio nanocomposites with interesting catalytic properties, based on chitosan and containing different amounts of gold nanoparticles is presented. The method only involves the use of the biopolymer chitosan and a precursor gold salt, without addition of supplementary reducing agents, the main stage of nanocomposites obtaining, takes place in solid phase induced only by heating. Highlights: Nanocomposites of chitosan with different amounts gold nanoparticles were prepared. Gold nanoparticles were generated in situ by a new heat-induced process in solid phase. It was possible to control the gold nanoparticles content and size in the nanocomposites. The catalytic effect of nanocomposites depend on the gold nanoparticles content. Abstract: A novel method to obtain catalytic bio-nanocomposites based on chitosan containing different amounts of gold nanoparticles generated in situ is reported. The formation of gold nanoparticles takes place in solid phase assisted by a heating induced process. This method only involves the use of chitosan biopolymer and a gold salt precursor. Unlike other methods the addition of external reducing and stabilizing agents to generate gold nanoparticles, is not needed because these roles are played by chitosan. Therefore, the striking properties of chitosan (e.g., high functionality, biodegradability and biocompatibility) are profited, in order to design a facile and green route of synthesis. Additionally, the described method allows to vary the amount and size of the gold nanoparticles contained in the bio-nanocomposite by using different gold ion compositions and temperatures of heating process. Finally, the bio-nanocomposite performance as heterogeneous catalyst on the reduction of p-nitrophenol (4-NP) to p-aminophenol (4-AP) as a model system was assessed. The results showed a significant catalytic effect that increases as the content of gold nanoparticles in the bio-nanocomposite also increases.